Immunosuppressive effect of mesenchymal stem cells on lung and gut CD8+ T cells in lipopolysaccharide‐induced acute lung injury in mice. (19th March 2021) - Xu, Yanping; Zhu, Jiaqi; Feng, Bing; Lin, Feiyan; Zhou, Jiahang; Liu, Jingqi; Shi, Xiaowei; Lu, Xuan; Pan, Qiaoling; Yu, Jiong; Zhang, Ying; Li, Lanjuan; et al.
Abstract: Objectives: Acute lung injury (ALI) not only affects pulmonary function but also leads to intestinal dysfunction, which in turn contributes to ALI. Mesenchymal stem cell (MSC) transplantation can be a potential strategy in the treatment of ALI. However, the mechanisms of synergistic regulatory effects by MSCs on the lung and intestine in ALI need more in‐depth study. Materials and methods: We evaluated the therapeutic effects of MSCs on the murine model of lipopolysaccharide (LPS)‐induced ALI through survival rate, histopathology and bronchoalveolar lavage fluid. Metagenomic sequencing was performed to assess the gut microbiota. The levels of pulmonary and intestinal inflammation and immune response were assessed by analysing cytokine expression and flow cytometry. Results: Mesenchymal stem cells significantly improved the survival rate of mice with ALI, alleviated histopathological lung damage, improved intestinal barrier integrity, and reduced the levels of inflammatory cytokines in the lung and gut. Furthermore, MSCs inhibited the inflammatory response by decreasing the infiltration of CD8 + T cells in both small‐intestinal lymphocytes and Peyer's patches. The gut bacterial community diversity was significantly altered by MSC transplantation. Furthermore, depletion of intestinal bacterial communities with antibiotics resulted in more severe lung and gut damages and mortality, while MSCs significantly alleviated lung injury due to their immunosuppressive effect. Conclusions: The present research indicates that MSCs attenuate lung and gut injury partly via regulation of the immune response in the lungs and intestines and gut microbiota, providing new insights into the mechanisms underlying the therapeutic effects of MSC treatment for LPS‐induced ALI. Abstract : This study focuses on the protective effects of mesenchymal stem cells (MSCs) in the lung and gut of Lipopolysaccharide‐induced acute lung injury mice. The data suggest that MSCs improved intestinal barrier function and reduced intestinal infiltration of CD8 + T cells. Further, depletion of intestinal bacterial communities with antibiotics significantly improved the therapeutic effects of MSCs.